GROWTH AND PRODUCTION OF SHALLOT (Allium ascalonicum L.) WITH GUANO ORGANIC FERTILIZER AND TRICHODERMA SP APPLICATION - Widuri, Laily Ilman; Amalia, Dita; Fariroh, Indri; Harsanti, Restiani Sih; Slameto, Slameto (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Shallot (Allium ascalonicum L.) is an important horticultural commodity with high economic value, but its productivity has declined, especially in several production centers, including Probolinggo Regency. Disease attacks are one of the factors causing the decline in production, prompting farmers to use chemicals to control the disease. The use of chemical fungicides frequently poses risks to the environment and food safety, thereby highlighting the need for eco-friendly alternatives such as biological agents (e.g., Trichoderma sp.) and organic fertilizers like guano. This study aimed to determine the effect of Trichoderma sp. and guano fertilizer on the growth and yield of shallots. The study used a Factorial Randomized Block Design (RBD) with the first factor being the dose of Trichoderma sp 0 (T1), 15 (T2), 25 (T3), 35 (T4) g/plant, and the second factor was guano fertilizer treatment at doses of 0 (G1), 35 (G2), 45 (G3), and 55 (G4) g/plant. The results showed that there was no interaction between Trichoderma sp. and guano fertilizer treatments on the growth and yield of shallots. However, both separately had a significant effect on several growth and yield parameters. Guano fertilizer had a significant effect on crown height, stem diameter, fresh and dry bulb weight, and root volume with an optimum dose of 45 g/plant. Meanwhile, the application of Trichoderma sp. had a significant effect on bulb diameter. The combination of biological agents and organic fertilizers demonstrated significant potential to enhance shallot productivity in a sustainable and environmentally responsible way. Keywords: Biofertilizer, Biological agents, Environmentally friendly, Organic fertilizer,